Structural transformations of the material and technical resources of the dermatovenereological service in the Russian Federation in the period 2010–2020 and their effect - Alexey A. Kubanov; Lidia E. Melekhina (Vestnik Dermatologii i Venerologii, 2022)
Background. The quality and availability of medical care to the population directly depends on the organization of the treatment and diagnostic process, which is directly related to the material and technical resources of medical organizations.